2022
DOI: 10.1111/ecc.13569
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic burden of disease: Survivorship costs for renal cell carcinoma

Abstract: Objective The objective of this study is to assess the risk‐stratified 10‐year socio‐economic burden of renal cell carcinoma (RCC) follow‐up costs after initial treatment in Germany from 2000 to 2020. Methods A micro‐costing method considering direct and indirect medical expenditure associated with follow‐up procedures was employed to calculate survivorship costs per patient. The frequencies of physician–patient visits, examinations and diagnostic tests were extracted from guidelines, whilst expenses were sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…15 Although gastrointestinal malignancies are a heterogeneous group, this cost analysis showed that most health expenditures occurred in the inpatient setting and that the most significant increases in health Europe. 29 The treatment landscape of mRCC has been changing rapidly since several trials have gotten underway to evaluate the treatment efficacy of newer TKIs, ICIs, and their combinations. 30 The cost-effectiveness of these systemic therapies, the management of adverse events, and the complications of the disease will need to be carefully assessed to optimize service utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although gastrointestinal malignancies are a heterogeneous group, this cost analysis showed that most health expenditures occurred in the inpatient setting and that the most significant increases in health Europe. 29 The treatment landscape of mRCC has been changing rapidly since several trials have gotten underway to evaluate the treatment efficacy of newer TKIs, ICIs, and their combinations. 30 The cost-effectiveness of these systemic therapies, the management of adverse events, and the complications of the disease will need to be carefully assessed to optimize service utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Because the overall worldwide cancer burden is expected to rise by >40% in the next 20 years, efficient resource allocation for patients with kidney cancer carries importance in future health policy design 1 . The economic burden of managing kidney cancer, particularly RCC, has gradually increased over time in the United States 21 as well as in Europe 29 . The treatment landscape of mRCC has been changing rapidly since several trials have gotten underway to evaluate the treatment efficacy of newer TKIs, ICIs, and their combinations 30 .…”
Section: Discussionmentioning
confidence: 99%